The NOS3 G894T (rs1799983) and -786T/C (rs2070744) polymorphisms are associated with elite swimmer status - Zmijewski, P.; Cieszczyk, P.; Ahmetov, I. I.; Gronek, P.; Lulinska-Kuklik, E.; Dornowski, M.; Rzeszutko, A.; Chycki, J.; Moska, W.; Sawczuk, M. (Biology of Sport, 2018)
Endothelial nitric oxide synthase (NOS3) generates nitric oxide in blood vessels and is involved in the regulation of vascular function, metabolism and muscle fibre type transformations. Evidence suggests that the NOS3 G894T (rs1799983) and -786T/C (rs2070744) polymorphisms are associated with athletic performance. The purpose of this study was to determine the association between the NOS3 G894T and -786T/C polymorphisms with elite swimmer status in Polish athletes. One hundred and ninety-seven Polish swimmers (104 males and 93 females), who competed in national and international events, and 379 healthy control subjects (222 males and 157 females) were recruited for this study. The swimmers were divided into two groups: short distance swimmers (SDS; n=147; 50-200 m) and long distance swimmers (LDS; n=49; more than 500 m). As expected, the frequencies of the -786T/C T allele (77.0 vs. 63.1%, p = 0.0085) and G-T haplotype (63.7 vs. 52.0, p=0.025) were significantly higher in the LDS group in comparison with controls. Compared with the -786T/C CC genotype, the chance of being a long distance swimmer was 8.49 times higher (CI=1.14-62.78, p=0.023) for the carriers of -786T/C T allele than in control subjects. On the other hand, the Asp allele frequency was significantly higher in the female SDS group compared with controls (34.3 vs. 18.5%, p=0.00043). In conclusion, our results demonstrate that the T allele and the G-T haplotype of the -786T/C and G894T polymorphisms may be beneficial for long distance swimmers.